2022
DOI: 10.1007/s12185-022-03514-6
|View full text |Cite
|
Sign up to set email alerts
|

Long-term safety profile of tirabrutinib: final results of a Japanese Phase I study in patients with relapsed or refractory B-cell malignancies

Abstract: Tirabrutinib is a Bruton’s tyrosine kinase inhibitor for treating B-cell malignancies. We report the final results of a Phase I study of tirabrutinib in 17 Japanese patients with B-cell malignancies. Patients were administered tirabrutinib at a dose of 160 mg, 320 mg, or 480 mg once daily, or 300 mg twice daily (N = 3, 3, 4, and 7, respectively). Three patients continued tirabrutinib until study completion (November 30, 2020). Adverse events (AEs) occurred in all 17 patients, with Grade 3–4 AEs in 8 (47.1%), s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 33 publications
0
1
0
Order By: Relevance
“…Tirabrutinib is an irreversible and covalent BTKi. Administered in a Japanese study in patients with B-cell lymphoproliferations, it was shown to result in an ORR and a median duration of response of 76.5% and 2.59 years, respectively (43).…”
Section: Covalent Btkismentioning
confidence: 99%
“…Tirabrutinib is an irreversible and covalent BTKi. Administered in a Japanese study in patients with B-cell lymphoproliferations, it was shown to result in an ORR and a median duration of response of 76.5% and 2.59 years, respectively (43).…”
Section: Covalent Btkismentioning
confidence: 99%